"The Land under the White Wings": The Romantic Landscaping of Socialist Belarus. Issue 1 (2nd January 2017) - Gapova, Elena
Abstract : This essay explores the imaginative transformation of quintessentially socialist Soviet Byelorussia into a romantic and sacred "land of castles." The romantic landscaping, performed in the 1960s by intellectuals and especially the writer Uladzimir Karatkevich, changed the meaning of the land by creating a site parallel to the socialist republic, the land of intellectual and moral pursuits that can sustain life's meaning. This romantic shift also points to changes in the texture of Soviet society, as new types of elites—intellectuals and literati—sought to contest the Communist party's agenda of man's being in the world. The "really existing socialism" witnessed an emergence of new ideas regarding national space and landscape that legitimized nonsocialist historical consciousness: inspired individuals, rather than the working class, were emerging as subjects of history and agents with a mission.